Enhanced weak force sensing based on atom-based coherent quantum noise cancellation in a hybrid cavity optomechanical system - Singh, S. K.; Mazaheri, M.; Peng, Jia-Xin; Sohail, A.; Khalid, Mohammad; Asjad, M. (Frontiers in Physics, 2023)
The weak force-sensing based on coherent quantum noise cancellation (CQNC) scheme is presented in a hybrid cavity optomechanical system containing a trapped ensemble of ultracold atoms and an optical parametric amplifier (OPA). In the proposed system, the back action noise can be completely eliminated at all frequencies as well as through the proper choice of the OPA parameters, the noise spectral density can be also reduced at lower frequencies. This leads to a significant enhancement in the sensitivity of cavity optomechanical weak force sensor and also the noise spectral density surpasses the standard quantum limit (SQL) even for small input power at lower detection frequency. Further, the experimental feasibility of this scheme is also briefly discussed. This study can be used for the realization of force sensor based on hybrid cavity optomechanical systems and for coherent quantum control in macroscopic systems.